An auction for collaborative vehicle routing: Models and algorithms - Vincentius C. G. Karels; Lucas P. Veelenturf; Tom Van Woensel (EURO Journal on Transportation and Logistics (EJTL), 2020)
Increasing competition and expectations from customers pressures carriers to further improve efficiency. Forming collaborations is essential for carriers to reach their targeted efficiency levels. In this study, we investigate an auction mechanism to facilitate collaboration amongst carriers while maintaining autonomy for the individual carriers. Multiple auction implementations are evaluated. As the underlying decision problem (which is a traditional vehicle routing problem) is known to be NP-hard, this auction mechanism has an important inherent complexity. Therefore, we use fast and efficient algorithms for the vehicle routing problem to ensure that the auction can be used in operational decision making. Numerical results are presented, indicating that the auction achieves a savings potential better than the thus far reported approaches in the literature. Managerial insights are discussed, particularly related to the properties of the auction and value of the information.
Keywords: 330; Vehicle routing problem; Horizontal collaboration; Auction; Algorithms; Request exchange